Imprisonment as a form of punishment: a case study of Maldives - shafy, mohamed; Wan Muhammad, Ramizah (Asian and African Research Centre (AARC), 2018)
Today punishment of imprisonment is seen to be given a less prominent significance in terms of punishing offenders as a means of rehabilitation and reducing recidivism rates throughout the world. However, it is found that the Maldivian courts have adopted a pattern of punishing offenders through imprisonment as a general form of punishment for almost all types of crimes despite considering the severity and mitigating factors of a given case. This pattern of punishing offenders through imprisonment alone is practiced by an authority of discretion given to the judges in the Penal Code of Maldives even though the same Penal Code allows for the application of other forms of alternative punishments. Whilst some may argue on the effectiveness of imprisonment as a general form of punishment, our argument lies in resorting away from a punishment that yields less possible avenues for rehabilitation and reintegration of offenders back into the society and that the preference should be given to alternative forms of punishments based on the circumstances surrounding any individual case.